THE BLACK FLY SIMULIUM (EUSIMULIUM) SMARTI N SP (DIPTERA: SIMULIIDAE) OF THE ONCHOCERCOSIC ZONE OF THE STATE OF CHIAPAS MEXICO - VARGAS, LUIS (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1974)
Investigation of the most favorable conditions for obtaining nicotine sulfate from tobacco waste, using the method of steam distillation in alkaline media, neutralizing the distillate to form nicotine sulfate, and concentrating this salt in acid soln A y
PUERTO RICO J PUBL HEALTH TROP MED
Keywords: FLY, SIMULIUM, DIPTERA, SIMULIIDAE, ONCHOCERCOSIC, CHIAPAS, MEXICO; CIENCIAS MEDICAS; SALUD PUBLICA; SALUD PUBLICA GENERAL